Determinan dan Konsekuensi Carbon Emission Disclosure - Ambarwati Ambarwati (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
This study aims to determine the effect of company characteristics on carbon emission disclosures and the effect of carbon emission disclosure on stock prices. The characteristics of the company in question are leverage, profitability and company age. The companies used as samples are oil, gas and coal companies in Non-Annex 1 member countries listed in the Osiris database. The observation period is from the start of the second commitment of the Kyoto Protocol. WarpPLS 7.0 application used to analyze data in this research. The test results show that leverage and company age have positive effect on carbon emission disclosure, whereas profitability has a positive effect on carbon emission disclosure but not significant. Furthemore carbon emission disclosure has a positive effect on stock prices.